2018
DOI: 10.1159/000495170
|View full text |Cite
|
Sign up to set email alerts
|

Adipose TSHB in Humans and Serum TSH in Hypothyroid Rats Inform About Cellular Senescence

Abstract: Background/Aims: Thyroid hormones have been recently linked to senescence and longevity. Given the recent description of TSHB mRNA in human adipose tissue (AT), we aimed to investigate the relationship between local AT TSH and adipose tissue senescence. Methods: TSHB mRNA (measured by real-time PCR) and markers of adipose tissue senescence [BAX, DBC1, TP53, TNF (real-time PCR), telomere length (Telo TAGGG Telomere Length Assay) and lipidomics (liquid chromatography mass spectrometry)] were analysed in subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Consequently, one hypothesis would be that prenatal THs could elongate telomeres early in life through the activation of the telomerase enzyme. The positive correlation found between the mRNA expression of the thyroid-stimulating hormone and telomere length in human adipose tissue could support such an hypothesis (13).…”
Section: Main Textmentioning
confidence: 81%
“…Consequently, one hypothesis would be that prenatal THs could elongate telomeres early in life through the activation of the telomerase enzyme. The positive correlation found between the mRNA expression of the thyroid-stimulating hormone and telomere length in human adipose tissue could support such an hypothesis (13).…”
Section: Main Textmentioning
confidence: 81%
“…It has been observed in animal and cell models that the activation of TSH receptors was related to the lipolysis of white adipose tissue and the accumulation of TG. Therefore, the activation of TSH receptors in adipose tissue may affect the distribution of body fat 27,28 . In addition, some studies reported that the relationship between TSH and systemic fat and obesity was likely mediated by leptin, which is a protein produced almost exclusively by fat cells that has been found to modulate the gene expression of thyrotropin‐releasing hormone in the paraventricular nucleus and thus increase the TSH releasing 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics technologies can be used to measure hundreds of lipids in human biofluid or tissue [12,24]. However, few lipidomic analysis have been performed on human adipose tissue [25,26,27]. Lipidomics is a platform-dependent technique and numerous sample preparation methods have been reported [28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%